Simulation study of medical isotope production using electron accelerator-driven photoneutron source - ZHANG Zixiong; LI Kaixuan; WEI Qianglin; LIU Yibao; ZHANG Qintuo (He jishu)
BackgroundPhotonuclear reactions and compact neutron sources have emerged as promising tools for the production of medical isotopes, providing alternatives to conventional reactor-based high-enriched uranium methods. East China University of Technology (ECUT) is currently constructing an electron accelerator-driven photoneutron source (ECANS) for medical isotope production research.PurposeThis study aims to investigate the photonuclear reaction with 100Mo isotope and utilize the generated neutrons for isotopic production.MethodsFirstly, the photonuclear reactions of 100Mo was analyzed in details. The neutron spectrum and activation yield of 99Mo within a high purity 100Mo target were investigated. Then, a new model to produce medical isotopes was established on the basis of the ECANS photonuclear source, comprising neutron energy modulation layer and neutron reflection layer. Finally, the production yields of 99Mo, 177Lu, and 90Y in various natural oxides were calculated and the feasibility of using photonuclear sources for medical isotope production was assessed. The content of radioactive impurities in natural oxides under irradiation conditions was also analyzed.ResultsSimulation results demonstrate that photo-nuclear reactions can effectively produce medical isotopes such as 99Mo, 177Lu, and 90Y, with respective activities of 0.64 TBq·d-1, 0.67 TBq·d-1, and 2.11 TBq·d-1. And in the high purity 100Mo target, the daily output of 99Mo reaches 2.00 TBq·d-1.ConclusionsThis study demonstrates the feasibility of using the photodisintegration reaction of 100Mo as a neutron source for secondary production of medical isotopes, offering the potential to enhance the economic viability of isotope production. The approach of this study provides preliminary insights for subsequent separation and purification processes, hence has certain reference value for the development of tools for radioactive isotope production.